Development of an inventory of biomedical imaging physics learning outcomes for MRI radiographers. Issue 3 (August 2019) - Castillo, J.; Caruana, C.J.; Morgan, P.S.; Westbrook, C.; Mizzi, A.
Abstract: Introduction: MRI is highly physics based yet no research-based inventory of physics learning outcomes specific to MRI radiographers was found in the literature. The purpose of this study was the development of such an inventory using a multi-stakeholder, multi-disciplinary approach (as advised by the WHO) and which would support a previously published competence profile. Methods: The inventory was developed in two phases: Phase 1: Development of an initial version of the learning outcomes inventory required to be able to deliver the competences via an analysis of textbooks and literature and validated by a small (n = 3) expert advisory group Phase 2: Final validation carried out via a bigger (n = 15) international group of subject matter experts (SMEs). Consensus was achieved via a dichotomous web-based questionnaire. Results: At 70% level of consensus the expert group validated an inventory of biomedical physics learning outcomes consisting of 281 knowledge and skill statements. It is subdivided into two sections: 'fundamental' physics learning outcomes which are generic to all competences and 'additional' physics learning outcomes specific to each individual competence. Conclusion: The process used is sufficiently generic to be easily adapted to the development of physics learning outcome inventories in other specialties of radiography and for other healthcare professions whose work involves highly technological medical devices. As a result of this study, the current MRI curriculum would need to be revised as it was not based on a formal systematic research process and many learning outcomes are in fact missing. Highlights: The inventory inform about the physics knowledge and skill required for MRI services. The learning outcomes assists healthcare education institutions to update curricula. Use the learning outcomes as benchmark against which performance and qualifications are assessed. Inform competence assessment frameworks to facilitate progression of skill and life long learning. Inform students and radiographers of what knowledge and skills are expected during practice.